Pengaruh Citra Destinasi Terhadap Minat Kunjungan Ulang Wisatawan Di Pantai Pandawa, Bali - Arrahma Sulistyafani; I Gede Anom Sastrawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Pandawa Beach is one of the many famous beaches on Bali Island that located in Kutuh Village, South Kuta District, Badung Regency. Infrastructures and facilities have been provided by the managers. However, the management of the coast still looks irregular. This is a weakness that can affect the image of Pandawa Beach on the interest in return visit. Thus, this research was conducted to determine the level of significance of the influence of destination image on the interest in return visit to Pandawa Beach.In this study, the research method used is a quantitative approach. Primary data and secondary data are used as data sources. The data collection techniques used were observation, questionnaires, and documentation. The sampling technique used non-probablity sampling techniques and also used several data analysis techniques. This research is also limited to destination image concept, interest in revisiting concept, and tourists concept. The results of this research indicate that the existence of tourim on Pandawa Beach as a destination image has a strong enough influence on the interest in return visit to Pandawa Beach significantly.Keywords: Destination Image, Interest in Return Visit, Pandawa Beach